SALUTRACK: A smartphone application to evaluate and monitor injuries and health problems in athletes from the Balearic Islands - Sastre-Munar, A.; Romero-Franco, N. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
Athletes and coaches often normalize injuries and pain to gain sports performance. Consistent supervision of workload and psycho-physiological aspects may prevent injuries and maximize performance, mainly integrating insights from healthcare and sports. Although these aspects could be facilitated through smartphone devices, no smartphone applications (apps) have been designed to monitor these aspects of the athlete experience. This study aimed to evaluate the capability of an app to collect sports and health data and identify areas for app enhancement. An observational study was designed to test the app (named: SaluTrack). Eleven young athletes, eight males and three females, were invited to participate. During 5 weeks, all participants used the app to complete four questionnaires periodically: wellness, pain, urinary incontinence (UI), and catastrophizing. The questionnaires were completed by 90.9% of participating athletes periodically. Regarding the wellness questionnaire, athletes responded with 10.94 ± 4.37 as the average rating. Regarding pain, all athletes who completed the questionnaire affirmed to have pain (3.63 ± 1.73), the knee being the anatomical region most affected (26.67%). Also, 27.27% of athletes affirmed to have UI. Regarding catastrophizing level, athletes showed 8.91 ± 9.02 points. Regarding qualitative feedback from athletes, we received three comments, all positive aspects gained from using this tool. SaluTrack showed to be an appropriate app to easily collect sports and health data from athletes related to wellness, pain, UI, and catastrophizing. This methodology is useful for weekly monitoring of potential injury risk and to improve coaching staff`s communication with athletes.